Dari Surau ke Madrasah : Modernisasi Pendidikan Islam Di Minangkabau 1900-1930 M - Satria, Rengga (TADRIS: Jurnal Pendidikan Islam, 2019)
This study concludes that the modernization movement of Islamic education that occurred in Minangkabau in the period 1900-1930 caused the "disappearance" of its function as a traditional Islamic education institution in Minangkabau. Madrasa system then introduced by ulama kaum muda to replace surau as Islamic education institution. Through the madrasa system, ulama kaum muda have succeeded in dialogue the modernity with Islam. This research is a library research using qualitative methods with a socio-historical approach. Through this socio-historical approach, the author does not only want to present this research in a factual descriptive manner, but also tries to reveal facts through an analysis-critical perspective.